2002
DOI: 10.1128/mcb.22.13.4781-4791.2002
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of a Gamma Interferon Response: Expression and Assembly of CIITA Promoter IV and Inhibition by Methylation

Abstract: Chromatin immunoprecipitation assays were employed to assess the kinetics of transcription factor assembly and histone modifications that occur during gamma interferon (IFN-␥) induction of CIITA gene expression. CIITA is the master regulator of major histocompatibility complex class II transcription. Promoter IV (PIV), the major IFN-␥ responsive promoter for CIITA expression, requires both STAT1 and IFN regulatory factor 1 (IRF-1) for induction by IFN-␥. STAT1 binding to PIV was detected first and was accompan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
129
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(145 citation statements)
references
References 49 publications
15
129
1
Order By: Relevance
“…The methylation around the transcription start site, which silenced CIITA-PIV gene expression, was in turn inversely related to histone acetylation, indicating a possible role for histone deacetylation in the gene silencing. This would be consistent with the findings of Morris et al (2002), who reported histone acetylation to be involved in the transcriptional regulation of CIITA.…”
Section: Discussionsupporting
confidence: 93%
“…The methylation around the transcription start site, which silenced CIITA-PIV gene expression, was in turn inversely related to histone acetylation, indicating a possible role for histone deacetylation in the gene silencing. This would be consistent with the findings of Morris et al (2002), who reported histone acetylation to be involved in the transcriptional regulation of CIITA.…”
Section: Discussionsupporting
confidence: 93%
“…The activation of the IFN-γ inducible CIITA promoter requires Stat1 and IRF-1 (MuhlethalerMottet et al, 1997;Piskurich et al, 1999;Morris et al, 2002). Based on our data and published studies, IFN-γ stimulation activates PKCδ, which in turn leads phosphorylation of Stat1 at serine 727.…”
Section: Discussionsupporting
confidence: 65%
“…Activated Stat1 dimerizes and translocates to the nucleus, where it binds to the GAS element in pIV (Shuai et al, 1994;Wen et al, 1995;Vinkemeier et al, 1996;Mowen et al, 2000;Darnell, 1997). Stat1 also controls IRF-1 expression, which in turn activates the CIITA promoter (Piskurich et al, 1999;Morris et al, 2002). Therefore, IFN-γ mediated activation of pIV requires both Stat1 and IRF-1.…”
Section: Introductionmentioning
confidence: 99%
“…In addtion, to promote the binding of TF to CIITA-PIV, IFNg also includes the acetylation of histones leading to an accessibility of CIITA-PIV. 28 Furthermore, a variety of signal transduction pathways, such as PKA, upregulates CIITA expression, which, in turn, enhances HLA class II antigen cell surface expression. 29 …”
Section: Regulation Of Hla Class II Antigen Expressionmentioning
confidence: 99%